NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL SEBELAS KARYA TERE LIYE - Siti Sara; Novi Cahya Dewi; Sri Nilawati (Samawa (Sakinah, Mawaddah Warahmah), 2026)
This study aims to describe in depth the character education values and methods embedded in the novel Sebelas by Tere Liye. This research utilizes a qualitative approach with library research through text study, focusing on interpreting the content and messages contained in the literary work. The primary data source in this study is the novel Sebelas, while secondary data sources are obtained from various books, scientific journals, and other relevant references related to character education and literary studies. Data collection techniques were carried out through document analysis by reading carefully, reviewing, and recording important parts related to character education values and methods. Furthermore, data analysis techniques used content analysis to systematically identify, classify, and interpret the collected data. Data trustworthiness is ensured through persistent observation and referential adequacy, ensuring that the study's results can be scientifically defended.The results show that there are various character education values in the novel Sebelas, including hard work, discipline, tolerance, and responsibility. These values are portrayed through the attitudes, behaviors, and interactions among the characters in the story. Additionally, character education methods were also found, which include exemplary methods (role modeling), habituation, reward and punishment, guidance and direction, i’tibar (taking lessons), tabayyun (clarification), and islah (reconciliation/improvement). These methods are conveyed through the storyline, conflicts, and resolutions experienced by the characters. Thus, the character education values and methods in the novel Sebelas not only convey explicit meanings but also hold strong relevance for application in education, particularly in shaping students' character. This novel can serve as an effective learning medium for instilling moral and character values in students through a contextual and engaging approach.